AN ANALYSIS OF FEMALE LEADERS IN BUDDHISM - Mrs. Nuengruethai Phunlap (Journal of Contemporary Buddhist Society = JCBS, 2022)
An analytical study of women leaders in Buddhism. The purpose was to study the role of women in Buddhism during the time of the Lord Buddha and to analyze the model of women leaders in Buddhism. This thematic paper was conducted through the Tipitaka, Commentaries. Sub-Commentaries, Texts and researches related to Buddhism. From the study, it was found that Women in Buddhism in the time of the Buddha had many roles in Buddhism, such as Mrs. Kesapdee Kottamee. who is the leader in asking for ordination as a nun Suchada's role in offering Madhupayas rice to Prince Siddhartha during his ascetic practice to attain enlightenment as Lord Buddha The role of Mrs. Visakha in fostering preserving Buddhism in the Buddha's time until it was nicknamed "Maha Upasika" As for the model of women leaders in Buddhism. it was found that women leaders were divided into two dimensions: 1) the dimension of maintaining Buddhism. There are many women who are religious leaders both in the country and abroad. In Thailand, there are 2 people who play a role in the preservation of Buddhism, namely Maechee Sansanee Sathirasuta, the founder of Sathira Dhammasathan. She is a model woman in in the preservation of the two Buddha dhammas of Phra Samma Sambuddhachao and another person is Dr. Uraisri Kanungsukkasem, who has patronized and maintained Buddhism all along: in politics, 2) women national leaders, 3) women business leaders, and 4) the most powerful women in the world.